2013
DOI: 10.12659/msm.889035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic accuracy of Doppler USG and contrast-enhanced magnetic resonance angiography and selective renal arteriography in patients with atherosclerotic renal artery stenosis

Abstract: BackgroundThere are many systemic complications of conventional selective renal arteriography (SRA), such as contrast-mediated nephropathy. Contrast-enhanced magnetic resonance angiography (CE-MRA) and renal artery Doppler ultrasonography (DUSG) have been used increasingly for renal artery stenosis (RAS). The aim of this study was to evaluate the accuracy of CE-MRA and DUSG as used for diagnosis of RAS.Material/MethodsWe divided 130 consecutive patients investigated for resistant hypertension into 2 groups bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Twelve of 25 studies reported accuracy as a main outcome. 12,14,[24][25][26][27][28][29][30][31]32,33 Six of those 12 studies reported high agreement with CVA, 14,30,33 SRA, 25,29 and MRA 24 (range: 81-98%). The remaining 6 of 12 studies reported either moderate, 28 low, 31 or a combination of the degree of agreement depending on the DUS parameter.…”
Section: Dus Versus Other Angiography Techniquesmentioning
confidence: 98%
See 2 more Smart Citations
“…Twelve of 25 studies reported accuracy as a main outcome. 12,14,[24][25][26][27][28][29][30][31]32,33 Six of those 12 studies reported high agreement with CVA, 14,30,33 SRA, 25,29 and MRA 24 (range: 81-98%). The remaining 6 of 12 studies reported either moderate, 28 low, 31 or a combination of the degree of agreement depending on the DUS parameter.…”
Section: Dus Versus Other Angiography Techniquesmentioning
confidence: 98%
“…For each statistic, heuristic thresholds of > 80%, 60% to 80%, and < 60% were considered high, moderate, and low agreement, respectively. 12 As outlined above, only studies post-2005 (≥ 2006) were included.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The gold standard for ARAS diagnosis is conventional renal angiography [ 22 ]. However, the measurements of the stenosis degree can be performed with less invasive techniques including DUS (sensitivity 84%, specificity 97%) [ 23 ], magnetic resonance angiography (MRA, sensitivity 92%–97%, specificity 73%–93%) [ 24 ] and/or computed tomographic angiography (sensitivity 59%–96%, specificity 82%–99%) [ 25 ]. DUS also allows monitoring of stent patency in cases with stent deployment.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Nevertheless, duplex US is highly dependent on the examiner skills and can be impeded by patients´ body habitus. Alternatively, cross-sectional imaging like computed tomography angiography (CTA) or magnetic resonance angiography (MRA) revealed high sensitivity and specificity rates in the assessment of RAS [ 3 5 ]. Performance of non-invasive diagnostic assessment prior to invasive management might be useful in providing information regarding anatomical variants and characteristics of the stenosis.…”
Section: Introductionmentioning
confidence: 99%